A tiered approach to assess effects of diclofenac on the brown mussel Perna perna: A contribution to characterize the hazard. (1st April 2018) - Fontes, Mayana Karoline; Gusso-Choueri, Paloma Kachel; Maranho, Luciane Alves; Abessa, Denis Moledo de Souza; Mazur, Wesley Almeida; de Campos, Bruno Galvão; Guimarães, Luciana Lopes; de Toledo, Marcos Sergio; Lebre, Daniel; Marques, Joyce Rodrigues; Felicio, Andreia Arantes; Cesar, Augusto; et al.
Abstract: Pharmaceutical discharges into the aquatic ecosystem are of environmental concern and sewage treatment plants (STPs) have been pointed out as the major source of these compounds to coastal zones, where oceanic disposal of sewage occurs through submarine outfalls. Diclofenac (DCF) is one of the most frequently detected pharmaceuticals in water, but little is known about the effects on marine organisms. In this study, we employed a tiered approach involving the determination of environmental concentrations of DCF in marine water and the adverse biological effects for fertilization, embryo-larval development and biomarker responses of the mussel Perna perna . Results indicate that effects in fertilization rate and embryo-larval development were found in the order of mg·L −1 . However, low concentrations of DCF (ng·L −1 ) significantly decreased the lysosomal membrane stability and COX activity, as well as triggered DNA damage, oxidative stress and changes in antioxidant defenses. Our results point to an environmental hazard at coastal ecosystems and suggest the need for improvements in the treatment of domestic wastewater aiming to reduce DCF concentrations, as well as regulation on current environmental legislation and monitoring of aquatic ecosystems. Graphical abstract: Image 1 Highlights: Toxicity to gametes and embryos exposed to Diclofenac. Cyto-genotoxicity in adult mussels exposed to ng·L-1 levels. Similar mode of action in a non-target organism. Adverse effects at environmentally relevant concentrations.